Emergence of Mycobacterium orygis: novel insights into zoonotic reservoirs and genomic epidemiology - Hugh, Benedict T.; Sim, Eby M.; Crighton, Taryn; Sintchenko, Vitali (Frontiers in Public Health, 2025)
Tuberculosis (TB), caused by members of the Mycobacterium tuberculosis complex (MTBC), is a significant global health threat, with millions of cases diagnosed annually and an annual death toll exceeding 1.6 million. Zoonotic TB (zTB), transmitted between animals and humans, remains poorly understood and difficult to control. This narrative review examined current evidence of the emergence and transmission pathways of Mycobacterium orygis, a recently defined member of MTBC. The structured searches for published literature and genome sequence with relevant metadata were conducted using NCBI PubMed and GenBank, respectively. Population diversity was investigated using phylogenomic analysis. Despite significant gaps in current laboratory diagnostic capacity for TB, M. orygis has been documented in 14 countries from 5 continents across 17 host species. Many cases (≈40%) were diagnosed around The Subcontinent and associated with a diverse range of mammalian hosts. In India, zTB due to M. orygis appeared to be more prevalent than disease associated with M. bovis (another zoonotic member of the MTBC). The whole genome sequencing of M. orygis isolates highlighted high diversity associated with different ecological niches. The increasing world-wide prevalence of M. orygis, especially in Asia, highlighted its emergence as a significant pathogen with zoophilic and anthropophilic potential. The reviewed evidence suggested multiple transmission pathways between humans and domesticated and wild mammalian hosts. Enhanced TB laboratory diagnostics and surveillance are imperative for mitigating the spread of zTB including one caused by M. orygis in areas of established and currently unrecognized endemicity.